A Comparison On Neural Network Forecasting. - Ong, Hong Choon; Chan, Shin Yue (2011)
This study compares the effectiveness of the Box-Jenkins model and neural networks model in making a forecast. An eighteen years bimonthly water consumption in Penang data set is analyzed. Multilayer perceptron (MLP) in neural network with single hidden layer and double hidden layers using errorbackpropagation algorithm models are used.